MANAJEMEN HOTEL DI LOMBOK NTB DALAM BRANDING PARAWISATA HALAL UNTUK MENARI PENGUJUNG TAHUN 2018 - Muhamad Ari Arifin (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2023)
West Nusa Tenggara, which is one of the priorities in the development of halal tourism, seeks various strategies to perfect the wishes of the government. Based on data from the Central Statistics Agency, as known by Hassanuddin, Lombok is one of the favorite tourist destinations in Indonesia, with the number of visitors reaching 3.5 million people in 2017, the hotel management strategy in branding halal tourism to attract visitors in 2018 and the impact the existence of halal tourism branding on hotels in Central Lombok in attracting visitors in 2018. This study uses a descriptive qualitative methodology using a phenomenological method of field research, in which this study seeks to understand the meaning of an event and its interplay with humans in situations in the form of a field, namely by going directly to the field to explore governance, describing or describing. The hotel management strategy in 2018 in the application of destination branding by the NTB government continues to use the basic principles of sharia by referring to what has become a provision in Islamic values ​​and the impact of halal tourism branding on Central Lombok hotels in attracting visitors in 2018. very influential on the level of visitor interest and income there was a decrease in turnover due to the devastating earthquake that hit the Lombok area until the end of the year..